(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
We present a taxonomic and palaeoecological analysis of a continental mollusc fauna from a mammoth-bearing succession near Bullendorf in Lower Austria. The taxonomic analysis comprises morphological descriptions and SEM documentation of 15 Pleistocene gastropod species. A Principal Component Analysis of the quantitative and qualitative composition of the investigated samples reveals a stratigraphic succession of four mollusc assemblages defined herein as Galba truncatula assemblage, Succinella oblonga assemblage, Pupilla muscorum/loessica and Pupilla alpicola/sterrii assemblages. The autecological requirements of the species of each assemblage allow a reconstruction of the palaeoenvironmental history of the section with alternating dry and humid conditions within a general cooling trend. Despite generally low mollusc density and species richness, the Bullendorf site allows important insight into latest Quaternary regional environmental conditions and climate. Based on the comparison with similar mollusc sites across Europe, a biostratigraphic correlation with the Late Pleistocene ( 110–12 ka) is proposed.